PENDIDIKAN AGAMA DAN BUDI PEKERTI DALAM KURIKULUM 2013 (ANALISIS TEORITIS DAN PRAKTIS) - M. Yusuf Aminuddin M. Yusuf Aminuddin (Universitas Yudharta Pasuruan, 2017)
Moral decadence that occur today are not only struck in adults in various professions and jabatanya, but also has hit young people especially students young shoots that are expected to continue the struggle for truth, justice and peace in the future. Things like that are worrying for their educatiCon practitioners. Virtuous character is the embodiment of experience / execution of religious teachings. No virtuous character means not implement the teachings of the religion. So that each generation / individual is able to noble virtuous character then need to be educated about what and how well-mannered good. Therefore, moral education / moral education is obligatory. Forming a noble character behavior is not easy as open palms but a responsibility that must be done together to form good behavior for learners. Curriculum 2013 is to support the learning process in a briefing prepared for the learners are able to compete for future see the real state of globalization and in line with the increase in the advance of technology in the modern era of the all